Impact of the COVID-19 pandemic on therapeutic interventional oncology procedures and diagnostic CT/MRI examinations at a German university hospital - Nebelung, Heiner; Radosa, Christoph Georg; Schön, Felix; Blum, Sophia Freya Ulrike; Böhme, Christian; Hoffmann, Ralf-Thorsten; Plodeck, Verena (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2023)
Purpose The COVID-19 pandemic led to the implementation of severe restrictions on public life in Germany and a reduction in the number of non-COVID patients presenting for care. The aim of this study was to measure the impact on the number of therapeutic interventional oncology procedures in relation to diagnostic imaging studies at a high-volume radiology department.Materials and Methods The numbers of therapeutic interventional oncology procedures and diagnostic CT/MRI examinations for the years 2010 to 2021 were extracted using the hospital information system. Monthly data from January 2010 to December 2019 were used to build forecasting models for the timeframe from January 2020 to December 2021. Real procedure numbers were compared with predicted numbers to calculate residual differences, which were considered statistically significant if the real number was outside the 95 % confidence interval (p < 0.05).Results During the first German lockdown (March/April 2020), the number of outpatient CT/MRI examinations decreased significantly, with a less pronounced decrease of overall CT/MRI numbers. The second German lockdown (January-May 2021) led to lower than predicted outpatient CT numbers, whereas outpatient MRI numbers in part even exceeded predicted numbers and overall CT/MRI numbers stayed within confidence limits. The lockdowns had a more pronounced negative effect on the number of oncological MRI examinations compared to CT examinations. The number of therapeutic interventional oncology procedures showed no significant decrease during both lockdowns.Conclusion Lockdown measures had minor impact on the number of therapeutic interventional oncology procedures, possibly due to a shift from more resource-intensive therapies like surgery towards interventional oncology. The overall numbers of diagnostic imaging decreased during the first lockdown, while the second lockdown had less negative impact. The number of oncological MRI examinations was affected most severely. To avoid adverse outcomes, specific protocols for patient management during future pandemic outbreaks should be implemented and continuously adapted.Key Points Citation Format
Keywords: interventional procedures; MR-imaging; CT; COVID-19 pandemic